Distribution of galanin immunoreactivity in the respiratory tract of pig, guinea pig, rat, and dog. Issue 12 (December 1985) - Cheung, A; Polak, J M; Bauer, F E; Cadieux, A; Christofides, N D; Springall, D R; Bloom, S R
Abstract : Galanin, a newly discovered peptide isolated from porcine intestine, is known to cause contraction in rat smooth muscle preparations and to induce hyperglycaemia in dogs. By the use of radioimmunoassay and immunohistochemical techniques the concentration and distribution of galanin immunoreactivity were determined in several areas of the respiratory tract of five dogs, five guinea pigs, five rats, and two pigs. Antibodies were raised in rabbits to whole unconjugated natural porcine galanin. The highest galanin concentrations were found in the bronchus and the trachea of the dog, guinea pig, rat (2 pmol/g in each case), and pig (less than 1 pmol/g). The lowest galanin concentrations were found in the lung parenchyma. Gel chromatographic analysis in the pig showed one molecular form of galanin coeluting with the porcine galanin standard. By means of the indirect immunofluorescence technique on sections of tissues fixed in benzoquinone solution, galanin was found to be confined to nerve fibres in different regions of the respiratory tract. In the nasal mucosa of the pig nerve fibres containing galanin were distributed around seromucous glands and blood vessels and beneath the epithelium. In the trachea, bronchus, and major intrapulmonary airways of the pig, dog, and guinea pig galanin immunoreactive fibres were detected predominantly in smooth muscle, as well as around seromucous glands and in the adventitia of blood vessels. Rarely, galanin immunoreactive nerve fibres were found in the lung parenchyma. A few galanin immunoreactive ganglion cells also containing vasoactive intestinal polypeptide were found in the adventitia of the tracheobronchial wall of the pig and dog. The distribution of galanin suggests that it may have some influence on airway, vascular, and secretory functions in the mammalian respiratory tract.